2009
DOI: 10.1016/j.frl.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Value-at-Risk computation by Fourier inversion with explicit error bounds

Abstract: JEL classification: G10 G21 C63 C46 Keywords:Value-at-Risk Delta-gamma approximation Fourier inversion Characteristic function Error boundsThe Value-at-Risk of a delta-gamma approximated derivatives portfolio can be computed by numerical integration of the characteristic function. However, while the choice of parameters in any numerical integration scheme is paramount, in practice it often relies on ad hoc procedures of trial and error. For normal and multivariate t-distributed risk factors, we show how to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Bali, Mo, and Tang (2008) adopted the skewed generalized t ‐distribution with a time‐varying parameter for VaR estimation. Others using either parametric models with tail driven dynamics or non‐parametric techniques in the computation of VaR include Sun, Rachev, and Fabozzi (2009), Siven, Lins, and Szymkowiak‐Have (2009), Huang (2009), and Taamouti (2009).…”
Section: Var Methodologiesmentioning
confidence: 99%
“…Bali, Mo, and Tang (2008) adopted the skewed generalized t ‐distribution with a time‐varying parameter for VaR estimation. Others using either parametric models with tail driven dynamics or non‐parametric techniques in the computation of VaR include Sun, Rachev, and Fabozzi (2009), Siven, Lins, and Szymkowiak‐Have (2009), Huang (2009), and Taamouti (2009).…”
Section: Var Methodologiesmentioning
confidence: 99%
“…Considering the difference between multivariate normal distribution and multivariate t distribution in the description of market risk factors, Albanese and Campolieti (2006) proposed the probability density function for calculating the change of option portfolio value and the Monte Carlo simulation method for estimating the multivariate VaR at a given confidence level and explored the relationship between a normal distribution and a fat tail distribution. Like Glasserman (2004), Siven et al (2009) deduced the closed expression of moment generating function in the case of multivariate t distribution and compared Fourier-Inversion method with Monte Carlo simulation method. The results showed that the Fourier-inversion method was much quicker than Monte Carlo simulation method and that Fourier-Inversion was a good way to calculate option VaR.…”
Section: Figurementioning
confidence: 99%
“…see El-Jahel et al (1999). The Delta-Gamma method has been developed in terms of a Cornish-Fisher expansion in Jaschke (2002); in Glasserman et al ( 2001) Delta-Gamma is used to provide more efficient Monte Carlo simulated estimates of VaR; in Siven et al (2009) Delta-Gamma is used along with Fourier inversions to calculate VaR.…”
Section: Option Risk Measurementmentioning
confidence: 99%